Proposal to the European Commission for additional funding for BRAC NFPE phase III programme, June 2001- May 2004 - BRAC (© BRAC, 2016)
1. Introduction 2. Background 3. BRAC's strategy 4. LFA for the new short-term strategy 5. Financial summary and budget.